1999
DOI: 10.1254/jjp.80.67
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Vitamin K2 (Menatetrenone) on Bone Resorption in Ovariectomized Rats: A Histomorphometric and Dual Energy X-Ray Absorptiometric Study

Abstract: To clarify how vitamin K2 prevents bone loss in vivo, it was given to ovariectomized 20-week-old rats for 2 weeks. Bone mineral density (BMD) in the whole femur and in 7 specific portions (F1 to F7 from the proximal to the distal end) was determined by dual-energy X-ray absorptiometry, and histomorphometry was also performed in proximal tibial metaphysis. Ovariectomy (OVX) resulted in significant decreases in the BMD in the whole femur and the F1, F2, F6 and F7 portions. Histomorphometrical analysis of the tib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 22 publications
2
24
2
Order By: Relevance
“…Similarly, VK modulated Ob.S/BS and Oc.S/BS in the histomorphometric parameters. Although these changes were small, the present results suggest that VK increases the bone formation but suppresses the bone degradation in an osteoporosis model, as previously reported for the effect of VK (7,8,24,25). Of note, VK administration significantly decreases Glu-OC but increases Gla-OC in sera, possibly by acting on the OC metabolism.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly, VK modulated Ob.S/BS and Oc.S/BS in the histomorphometric parameters. Although these changes were small, the present results suggest that VK increases the bone formation but suppresses the bone degradation in an osteoporosis model, as previously reported for the effect of VK (7,8,24,25). Of note, VK administration significantly decreases Glu-OC but increases Gla-OC in sera, possibly by acting on the OC metabolism.…”
Section: Discussionsupporting
confidence: 88%
“…Previously, it has been reported that VK binds to the steroid and xenobiotic receptor and modulates the gene transcription in human osteoblastic cells (5,6). Additionally, VK plays roles not only in enhancing bone formation, but also in suppressing bone degradation (7,8). Clinically, VK has been shown to prevent bone loss and fractures in postmenopausal females with osteoporosis (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…All cancellous bone tissue between the traced lines was measured, with the exception of a ±0.3-mm-thick transitional zone lying between the cortical and cancellous bone tissue. The following parameters were measured as described before (48,49). The static parameters: trabecular bone volume /tissue volume (BV /TV, %), trabecular thickness (Tb.Th, mm), and trabecular number (Tb.N, / mm).…”
Section: Histological Analysesmentioning
confidence: 99%
“…Recent clinical studies have suggested that MK-4 effectively prevents the occurrence of new frac tures in patients with postmenopausal osteoporosis (6 -8) and ameliorates osteoporosis associated with Parkin son's disease (9). The effects of MK-4 on bone metabo lism were demonstrated in a model of postmenopausal osteoporosis (10)(11)(12). It is generally accepted that bone resorption is increased in ovariectomized rats.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that bone resorption is increased in ovariectomized rats. Various studies have suggested that MK-4 prevents, to some extent, the bone loss induced by ovariectomy by inhibit ing bone resorption (10,11). We reported that MK-4 protected against the loss of trabecular bone volume and its structure in rats rendered osteoporosic by sciatic neurectomy, through the process of maintaining bone formation (13 Three weeks after neurectomy, six neurectomized rats (SNx) and six sham-operated rats were sacrificed to obtain pre-administration data (day 21).…”
Section: Discussionmentioning
confidence: 99%